The Agrarian Life of the North 2000 BC AD 1000 Studies in Rural Settlement and Farming in Norway - Oma, Kristin Armstrong (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
The 14 articles presented in this publication represent some of the latest and most relevant research on rural settlement and farming from the Late Neolithic through the Early Medieval Period in Norway. It deals with the impact of climate change, plague and the AD 536â 7 volcanic event and some of the earliest farms north of the Arctic Circle. It provides new perspectives and archaeological evidence for the Viking age farm of Norway, differences in regional settlement structures of agrarian societies, the relation between houses and graves in the Iron Age, and varying food practices as indicators of societal change.